(Isocyano group)⋯lone pair interactions involving coordinated isocyanides: experimental, theoretical and CSD studies. Issue 7 (5th February 2020) - Mikherdov, Alexander S.; Katkova, Svetlana A.; Novikov, Alexander S.; Efremova, Mariia M.; Reutskaya, Elena Yu.; Kinzhalov, Mikhail A.
Abstract : Both carbon and nitrogen centers in the coordinated isocyano group are capable of acting as a π-hole donor toward lone pairs. Abstract : Inspection of the X-ray structure of the newly prepared trans -[PdCl(CNXyl)ADC] (ADC = XylNH–C̲N–[5-iodo-2, 6-dimethylpyrimidin-4-yl]) complex made it possible to identify for the first time the π-hole interaction involving the nitrogen atom of a coordinated isocyano group with a lone pair. Processing of available CSD data and results of DFT calculations revealed the possibility of two different sites for π-hole interaction involving isocyanides, i.e. both isocyano carbon and nitrogen centers are capable of acting as the π-hole donor toward lone pairs.